Persepsi Narapidana Atas Manfaat Hasil Belajar Dan Sosial Ekonomi Program Pelatihan Menjahit Di Lembaga Pemasyarakatan Klas Iia Wanita Semarang - Widiastuti Widiastuti; Amin Yusuf (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2021)
This study aimed to describe the perception of the benefits of learning outcomes inmates after attending training in sewing,Â  to describe the inmates perception of economy social benefits after training tailoring. The subjects included 8 consists of the coaching program Kasie independence, 1 instructor skills and 1 Institution correctional officer, 5 prisoners / inmates who attend training in sewing. The collection of data through observation, interviews, and documentation. The validity of the data using triangulation. The results showed the benefits of learning outcomes include: prisoners / inmates more regularly in life in Prison, can control emotions and tolerate each other, gain new knowledge and skills, more independent and more confident with new skills. Social benefits sewing training: developing social interaction, communication networks expand, develop social ties, personal growth, improving productivity. Economic benefit: finding a new job after being out of the Penitentiary, earning / premium, gaining entrepreneurial network.